2019
DOI: 10.7759/cureus.4177
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Epidural Neurosarcoidosis Causing Spinal Cord Compression: A Case Report

Abstract: We describe a rare case of multifocal extramedullary epidural neurosarcoidosis that presented with myelopathy without motor deficits and perform a literature review for previous cases of epidural neurosarcoidosis. A 46-year-old woman presented with lower back pain, urinary incontinence, gait disturbance, and sensory loss without motor deficits. Spine magnetic resonance imaging (MRI) showed multiple epidural lesions, the largest causing spinal cord compression at the T5 level. A computed tomography (CT)-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…At 1 week after discharge, her gait had improved markedly, and at 18 months after initial admission, she was ambulating without difficulty, neurologically intact, and employed. 23 Similarly, Nardon et al 25 also reported a case of an 80-year-old woman with cervical neurosarcoidosis who was also managed with 2 months of steroids with improved neurologic function and MRI demonstrating a resolution of epidural mass.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…At 1 week after discharge, her gait had improved markedly, and at 18 months after initial admission, she was ambulating without difficulty, neurologically intact, and employed. 23 Similarly, Nardon et al 25 also reported a case of an 80-year-old woman with cervical neurosarcoidosis who was also managed with 2 months of steroids with improved neurologic function and MRI demonstrating a resolution of epidural mass.…”
Section: Discussionmentioning
confidence: 94%
“… 22 , 26 Sarcoidosis has been described to manifest both in the vertebral bodies and within the spinal canal. 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 Those with intraspinal presentation are almost exclusively intradural sarcoidosis. 13 14 15 16 17 18 19 20 21 To the best of our knowledge, there are nine reported cases of intraspinal epidural sarcoidosis in the literature, including ours (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical management usually includes steroids (e.g., in some cases, require a prolonged course of steroid utilization) along with immunosuppressive medications(e.g., methotrexate). [3,4]…”
Section: Surgical Neurology International • 2020 • 11(133) |mentioning
confidence: 99%